`f(x)=x^2cosx, n=2, c=pi` Find the n'th Taylor Polynomial centered at c

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Taylor series is an example of infinite series derived from the expansion of `f(x)` about a single point. It is represented by infinite sum of` f^n(x)` centered at `x=c` . The general formula for Taylor series is:

`f(x) = sum_(n=0)^oo (f^n(c))/(n!) (x-c)^n`

or

`f(x) = f(c) + f'(c) (x-c)+ (f'(c))/(2!) (x-c)^2+ (f'(c))/(3!) (x-c)^3+ (f'(c))/(4!) (x-c)^4+...`

To determine the Taylor polynomial of degree `n=2` centered at `c=pi` , we may apply the definition of the Taylor series by listing the `f^n(x)` up to `n=2` .

`f(x) = x^2cos(x)`

Apply Product rule of differentiation: `d/(dx) (u*v) = v*du + u*dv` for each derivative.

`f'(x) = d/(dx) (x^2cos(x))`

Let `u = x^2` then `du =2x`

     `v = cos(x)` then `dv = -sin(x)`

`f'(x) =cos(x) *(2x) + x^2*(-sin(x))`

      `=2xcos(x)-x^2sin(x)`

`f^2= d/(dx)(2xcos(x)-x^2sin(x) )`

      `=d/(dx)2xcos(x)- d/(dx) x^2sin(x)`

 For `d/(dx)2xcos(x)` , we let:

`u = 2x` then `du =2`

`v = cos(x) ` then `dv = -sin(x)`

`d/(dx)2xcos(x)= cos(x)*2 + 2x*(-sin(x))`

                      `=2cos(x) -2xsin(x)`

 For `d/(dx)x^2sin(x)`  , we let:

`u = x^2` then `du =2x`

`v = sin(x) ` then `dv = cos(x)`

`d/(dx)2xcos(x)= sin(x)*2x + x^2*cos(x)`

                      `=2xsin(x) +x^2cos(x)`

Then, 

`d/(dx)2xcos(x)-d/(dx) x^2sin(x) = [2cos(x) -2xsin(x)] -[2xsin(x) +x^2cos(x)]`

              `= 2cos(x) -2xsin(x) -2xsin(x) -x^2cos(x)`

              `=2cos(x) -4xsin(x) -x^2cos(x)`

Thus, `f^2(x) =2cos(x) -4xsin(x) -x^2cos(x).`

Plug-in `x=pi` , we get:

`f(pi) =pi^2*cos(pi)`

        `=pi^2*(-1)`

        ` =-pi^2`

`f'(pi)=2pi*cos(pi)-pi^2*sin(pi)`

         `=2pi*(-1) -pi^2 *(0)`

         `=-2pi`

`f^2(pi) =2cos(pi) -4*pi*sin(pi) -pi^2*cos(pi)`

           `=2(-1) -4*pi*0 -pi^2*(-1)`

          `=-2+pi^2 or -(2-pi^2)`

Applying the formula for Taylor series centered at `c=pi` , we get:

`sum_(n=0)^2 (f^n(pi))/(n!)(x-pi)^n`

    `=f(pi) + f'(pi) (x-pi)+ (f'(pi))/(2!) (x-pi)^2`

    `=(-pi^2) + (-2pi) (x-pi)+ (-(2-pi^2))/(2!) (x-pi)^2`

    `= -pi^2 -2pi (x-pi)-(2-pi^2)/2 (x-pi)^2`

 The Taylor polynomial of degree `n=2 `   for the given function `f(x)=x^2cos(x)` centered at ` c=pi` will be:

`P(x) =-pi^2 -2pi (x-pi)-(2-pi^2)/2 (x-pi)^2`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial